Ocular phakomatoses in children - Grałek, Mirosława; Niwald, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
In the group of phakomatoses, four major disease syndromes are recognized: Sturge-Weber syndrome (angiomatosis encephalotrigeminalis), neurofibromatosis type 1 (peripheral form) and type 2 (central form), tuberous sclerosis (Bourneville disease), and von Hippel-Lindau disease (characterized by capillary malformations of the retina and cerebellum). They are defined by the presence of hamartoma-type tumors in various organs, including the visual system. This paper describes the general and ocular manifestations most commonly observed in these genetically determined disorders. In addition to medical history and physical examination, genetic testing and diagnostic imaging play an important role in diagnosis. Therapeutic management is tailored to the individual needs of each patient. Children with phakomatoses require regular ophthalmologic follow-up as well as multidisciplinary medical care.